Problematics of Arabic Language Learning at the End of Class Sessions in Hubulo Islamic Boarding Schools Gorontalo - Ratna Bt Hj Bahri; Khairus Sakinah Chaeruddin; Damhuri Damhuri (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
This study aims to analyze the problematics of Arabic language learning at the end of class sessions at Hubulo Islamic Boarding School, Gorontalo, to identify the factors contributing to these problems, and to examine their impact on students' achievement of Arabic language competencies. This research is a qualitative study employing a descriptive field study design. The research method used is a case study, focused on exploring learning dynamics during the final periods of Arabic instruction. The research subjects consist of Arabic language teachers and students at Hubulo Islamic Boarding School who participate in the intensive Arabic learning program, while the research object is the process of Arabic language learning at the end of class sessions. Data were collected through participatory classroom observation during final learning hours, in depth interviews with teachers and students, and documentation studies involving learning modules, evaluation records, and boarding school activity schedules. Data were analyzed using the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing verification. The results show that problems at the end of class sessions include decreased learning motivation, weakened concentration, limited variation in adaptive teaching methods, unconducive classroom conditions due to collective fatigue and noise, and the absence of rapid micro evaluation strategies. These conditions negatively affect students' mastery of vocabulary, grammar, and the four language skills. This study implies the need for adaptive, interactive pedagogical strategies such as language games, energizers, and micro evaluations to sustain student engagement and improve the effectiveness of Arabic learning at Hubulo Islamic Boarding School.